2000
DOI: 10.1016/s0014-5793(00)01181-9
|View full text |Cite
|
Sign up to set email alerts
|

ERK activation upon hypoxia: involvement in HIF‐1 activation

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a transcription factor activated by hypoxia. The HIF-1 activation transduction pathway is poorly understood. In this report, we investigated the activation of extracellular regulated kinases (ERK) in hypoxia and their involvement in HIF-1 activation. We demonstrated that in human microvascular endothelial cells-1 (HMEC-1), ERK kinases are activated during hypoxia. Using dominant negative mutants, we showed that ERK1 is needed for hypoxia-induced HIF-1 transactivation activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
302
7
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 353 publications
(334 citation statements)
references
References 29 publications
20
302
7
5
Order By: Relevance
“…15 However, phosphorylation also seems to play a role as it was shown that ERK1/2 MAPK are important to increase HIF-1 activity in hypoxia in some cell types. 17,18 Since HIF-1 activation by hypoxia occurs in all cell types while ERK1/ 2 is not important for this activation in all of them, other phosphorylation events may take place. In this work, we demonstrated that CK2 could be important for regulating HIF-1 activity in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 However, phosphorylation also seems to play a role as it was shown that ERK1/2 MAPK are important to increase HIF-1 activity in hypoxia in some cell types. 17,18 Since HIF-1 activation by hypoxia occurs in all cell types while ERK1/ 2 is not important for this activation in all of them, other phosphorylation events may take place. In this work, we demonstrated that CK2 could be important for regulating HIF-1 activity in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phosphorylation events also play a role as demonstrated by several studies: the activity of the MAP kinases ERK1/2 is needed for the transcriptional activity of HIF-1 but not for the stabilization of HIF-1a. 17,18 However, the C-terminal transactivation domain (TAD-C) of HIF-1a is not directly phosphorylated by ERKs 19 but a negative charge on threonine 796, located in the C-terminal transactivation domain of HIF-1a, seems to be essential for the interaction with CBP/p300 and hence for the activity of HIF-1. 20 These results suggest that kinases other than ERK1/2 could be involved.…”
mentioning
confidence: 99%
“…Although the link between the ERK and HIF pathway was identified soon after the discovery of HIFs, the nature of their interplay has remained less clear. Stabilised HIF-1 has been shown to be phosphorylated by p42/44 MAP kinases both under hypoxic conditions and in response to receptor-mediated ERK-activating stimuli [79][80][81]. The ERK-mediated phosphorylation was found to enhance the transcriptional activity of HIF-1 in various model systems, although the exact mechanism is still to be elucidated [82,83].…”
Section: Crosstalk With Erkmentioning
confidence: 99%
“…Multiple signalling pathways including the Ras/Raf/ ERK1/2 cascade have been shown to play a role in regulating HIF-1 activity and upregulating VEGF expression (Minet et al, 2000;Blancher et al, 2001;Hur et al, 2001;Sodhi et al, 2001;Fukuda et al, 2002;Lee et al, 2002;Mottet et al, 2002). Constitutive activation of the Ras/Raf/ERK1/2 pathway leads to the transformation of mammalian cells, and enhanced activity of this pathway occurs in many human cancers (Garnett and Marais, 2004;Wallace et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ERK1/2 has been shown to phosphorylate HIF-1a in vitro (Richard et al, 1999;Sodhi et al, 2001), whereas it has also been reported that ERK1/2 indirectly enhances HIF-1 activity by phosphorylating p300/CBP and increasing its ability to bind to HIF-1a (Sang et al, 2003). Previous studies have shown that the MEK1/2 inhibitor PD98059 or expression of dominant-negative (DN) forms of Ras, Raf or ERK1/2 all block HIF-1 activity to some degree in multiple cell types (Minet et al, 2000;Sodhi et al, 2001;Lee et al, 2002;Mottet et al, 2002). However, whether selective inhibition of ERK1/2 signalling blocks HIF-1 activity or whether ERK1/2 activation itself is essential for the induction of HIF-1a and activation of HIF-1 by hypoxia and growth factors is unclear.…”
Section: Introductionmentioning
confidence: 99%